Aktualisasi Budaya Inovasi Pada Organisasi Sektor Publik - Hidayah, Kemal; Kusumaningrum, Mayahayati; Wismono, Fani Heru; Amarullah, Rustan (Jurnal Borneo Administrator, 2018)
Innovation is the key to improve organizational performance. The development presently requires the actualization of innovation culture as a continuous improvement in the organizations' services. This paper presents an overview of the application of innovation culture in public sector organizations namely Investment and Integrated Licensing Offices (DPMPTSP) of Samarinda City, as well as factors that influence the success of actualizing the culture of innovation in this organization. This research is a qualitative research with a descriptive approach. The application of an innovation culture in DPMPTSP of Samarinda City has been relatively optimal, as evidenced by the various achievements and awards that have been achieved. Afterwards, the factors that influence the success of the actualization of innovation culture in DPMPTSP of Samarinda City are mainly by visionary and innovative leadership, reliable human resources, high team collaboration, and budget support. In addition, it can also be analyzed that the innovation culture in this organization has relatively implemented a holistic model of innovation culture. Keywords : Innovation, Innovation Culture, Organization, Public Service Abstrak Inovasi merupakan kunci untuk meningkatkan performa organisasi. Perkembangan zaman menuntut aktualisasi atas budaya inovasi sebagai perbaikan terus menerus atas pelayanan organisasi yang ada. Tulisan ini menyajikan gambaran mengenai penerapan budaya inovasi dalam organisasi sektor publik yakni DPMPTSP Kota Samarinda, serta faktor-faktor apa saja yang mempengaruhi keberhasilan aktualisasi budaya inovasi dalam organisasi tersebut. Penelitian ini merupakan penelitian kualitatif dengan pendekatan deskriptif. Hasil penelitian ini menunjukkan bahwa penerapan budaya inovasi di DPMPTSP Kota Samarinda relatif sudah berjalan optimal, terbukti dengan berbagai capaian dan penghargaan yang telah dihasilkan. Adapun faktor-faktor yang mempengaruhi keberhasilan aktualisasi budaya inovasi di DPMPTSP Kota Samarinda utamanya adalah kepemimpinan visioner dan inovatif, sumberdaya manusia yang handal, kerjasama tim yang tinggi, dan dukungan anggaran. Selain itu, juga dapat dianalisis bahwa budaya inovasi pada organisasi ini relatif sudahmenerapkan model holistik budaya inovasi. Kata Kunci : Inovasi, Organisasi, Budaya Inovasi, Pelayanan Publik